Application of Natural Colorants in Green Polyethylene Composites with Lignocellulosic Fillers: The Influence of Steam Sterilization on Mechanical Properties and Surface Quality - Anna Kufel; Stanisław Kuciel (Journal of Natural Fibers, 2022)
The concept of the presented research was to assess the applicability of natural colorants in dyeing biocomposites filled with natural fillers. As dyes, ground coffee, turmeric, couscous and ground paprika were used. Additionally, wood flour and walnut shell flour were added to improve strength parameters. The fillers were not dyed prior to processing, but the pigments were processed with the matrix and the filler. The optical observation and the influence of steam sterilization on mechanical properties were carried out, taking into consideration esthetics and performance of the product. The results showed that natural colorants can be successfully used to dye composites. Low-density biocomposites with increased rigidity were obtained. Composites were characterized by lower tensile strength than neat green polyethylene which was approximately 18 MPa. The high result for tensile modulus was obtained for composition with coffee – it increased to 2045 MPa.